Information Technology Resource Framework - Paska Marto Hasugian (Journal Majelis Paspama, 2024)
This research is a literature review that aims to investigate and analyze concepts and frameworks related to information technology resources. Through a literature review approach, this research collects, organizes, and analyzes previous research that has been conducted in this area. The main focus of this research is to gain an understanding of the role, components, and characteristics of the Information Technology Resource framework, as well as its impact on company performance. The method used in this research involved the search and selection of relevant scholarly articles, journals, and publications relating to the topic. After a careful selection process, literature studies that met the inclusion criteria were analyzed in detail, and important relevant information was retrieved for further analysis. The results of this literature review present various existing frameworks in the information technology resources domain. These frameworks cover important aspects such as information technology resource management, integration of information technology in business strategy, information technology performance measurement, and development of information technology competencies in organizations. In this context, this study identifies key concepts, theoretical perspectives, and recent trends in the development of information technology resource frameworks.